Archaeological investigations at South Quay, Hayle - Wolframm-Murray, Yvonne ca. 21. Jh (Archaeopress Publishing, 2023)
Archaeological work took place on South Quay, Hayle (Cornwall) between 2010-2014. The development of Hayle started in the mid-18th century and it soon became a significant industrial centre. This book extensively uses cartographic, photographic and documentary records to place the archaeological and structural features uncovered into context
Includes bibliographical references
Zielgruppe: Specialized
Keywords: Excavations (Archaeology) / England / Hayle; Hayle (England) / Antiquities